ASSESSMENT OF PSYCHOLOGICAL WELL-BEING AND PERSONAL MATURITY BY STUDENTS-PSYCHOLOGISTS - Шило, Оксана (SWorldJournal, 2021)
The article presents the results of studying the assessment of the concepts of "well-being" and "personal maturity" by students-psychologists. The repertory grid method was used, which allowed not only to evaluate the studied concepts, but also to identif